Clinical Experience of Patients Referred to a Multidisciplinary Cardiac Oncology Clinic: An Observational Study. (2nd August 2015) - Sulpher, Jeffrey; Mathur, Shrey; Graham, Nadine; Crawley, Freya; Turek, Michele; Johnson, Christopher; Stadnick, Ellamae; Law, Angeline; Wentzell, Jason; Dent, Susan
Abstract : Cardiotoxicity is the second leading cause of long-term morbidity and mortality among cancer survivors. The purpose of this retrospective observational study is to report on the clinical and cardiac outcomes in patients with early stage and advanced cancer who were referred to our multidisciplinary cardiac oncology clinic (COC). A total of 428 patients were referred to the COC between October 2008 and January 2013. The median age of patients at time of cancer diagnosis was 60. Almost half of patients who received cancer therapy received first-line chemotherapy alone (169, 41.7%), of which 84 (49.7%) were exposed to anthracyclines. The most common reasons for referral to the cardiac oncology clinic were decreased LVEF (34.6%), prechemotherapy assessment (11.9%), and arrhythmia (8.4%). A total of 175 (40.9%) patients referred to the COC were treated with cardiac medications. The majority (331, 77.3%) of patients were alive as of January 2013, and 93 (21.7%) patients were deceased. Through regular review of cardiac oncology clinic referral patterns, management plans, and patient outcomes, we aim to continuously improve delivery of cardiac care to our patient population and optimize cardiac health.